2019
DOI: 10.1097/j.pain.0000000000001760
|View full text |Cite
|
Sign up to set email alerts
|

New procedure of high-frequency repetitive transcranial magnetic stimulation for central neuropathic pain: a placebo-controlled randomized crossover study

Abstract: Repetitive transcranial magnetic stimulation (rTMS) is a procedure increasingly used to treat patients with central neuropathic pain, but its efficacy is still under debate. Patients with medically refractory chronic central neuropathic pain were included in 2 randomized phases (active/sham), separated by a wash-out period of 8 weeks. Each phase consisted of 4 consecutive rTMS sessions and a final evaluation session, all separated from one another by 3 weeks. High-frequency (20 Hz) rTMS was delivered over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 46 publications
1
45
0
1
Order By: Relevance
“…For central neuropathic pain (CNP), rTMS has been successfully applied to the M1 of the hemisphere contralateral to the pain site. Most recently, Quesada et al [37] demonstrated an analgesic effect of rTMS on CNP patients while using a longer stimulation period than any other study before it (roughly two months versus one to two weeks). Instead of utilizing the standard daily treatment approach, this study looked at the effects of "4 consecutive rTMS sessions over the course of 2 months."…”
Section: Repetitive Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…For central neuropathic pain (CNP), rTMS has been successfully applied to the M1 of the hemisphere contralateral to the pain site. Most recently, Quesada et al [37] demonstrated an analgesic effect of rTMS on CNP patients while using a longer stimulation period than any other study before it (roughly two months versus one to two weeks). Instead of utilizing the standard daily treatment approach, this study looked at the effects of "4 consecutive rTMS sessions over the course of 2 months."…”
Section: Repetitive Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…Stimulation of the primary motor cortex (M1) using repetitive transcranial magnetic stimulation (rTMS) is a noninvasive, safe method of stimulating the brain, [9][10][11] and several studies have investigated the analgesic effects of rTMS for various refractory disorders using different stimulation intensities, frequencies, number of pulses, and number of sessions. [12][13][14][15][16][17][18] We previously reported that M1 was a more effective stimulation target than other cortices, 19 high-frequency (5-or 10-Hz) rTMS was more effective than low-frequency (1-Hz) rTMS, 14 and the effects of a single session of rTMS were short-lasting. 20 Moreover, in our pilot randomized, blinded, controlled, crossover trial of patients with neuropathic pain in seven centers in Japan, ten daily rTMS treatments produced transient, modest pain relief.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that rTMS is promising treatment option for many neuropsychiatric conditions like depression, 2,24,25 OCD, 28 BD, 36,37 negative symptoms 29 and auditory hallucinations 30,31 in schizophrenia, addiction,s [33][34][35] anxiety and anxiety related disorders, [39][40][41] fibromyalgia, 44,45 chronic pain, 42,43 and dementia/Alzheimer's disease. [46][47][48][49] It is also very important that many studies reported that rTMS causes significant improvement of cognition.…”
Section: Resultsmentioning
confidence: 99%
“…42 A recent study showed that four consecutive HF-rTMS sessions (20 Hz ) every 3 weeks in the primary motor cortex have as a result a sustained analgesic effect. 43 HF-rTMS over the primary motor cortex in patients with fibromyalgia produce positive long-lasting improvements in their quality of life and reduction of chronic pain. rTMS is an effective treatment for fibromyalgia patients without adverse effects on pain and mood levels.…”
Section: Addictionsmentioning
confidence: 97%